2015
DOI: 10.1039/c5cp00043b
|View full text |Cite
|
Sign up to set email alerts
|

Detection of functional hydrogen-bonded water molecules with protonated/deprotonated key carboxyl side chains in the respiratory enzyme ba3-oxidoreductase

Abstract: The protonation/deprotonation of active carboxyl side chains by water networks forming the proton loading and exit sites in proteins are important steps in protein catalysis. An excellent system to study such basic principles is the heme-copper ba3 from T. thermophilus because it utilizes one proton input channel and it delivers protons to the active site for both O2 chemistry and proton pumping. We report the interaction of the heme a3 Fe propionate-A and the Asp372-His376 pair which forms the valve for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Based on the crystal structure cytochrome ba 3 from Thermus thermophilus contains a homodinuclear copper center (Cu A ), a low-spin heme b , and a heme a 3 -Cu B center [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. Cytochrome ba 3 catalyzes the reductions of oxygen (O 2 ) to water (H 2 O) and of nitric oxide (NO) to nitrous oxide (N 2 O), as well and the oxidation of carbon monoxide (CO) to carbon dioxide (CO 2 ) [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. The photolyzed ba 3 -CO species is an excellent model for time-resolved spectroscopic studies [7,8,9,13,15,18,24].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the crystal structure cytochrome ba 3 from Thermus thermophilus contains a homodinuclear copper center (Cu A ), a low-spin heme b , and a heme a 3 -Cu B center [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. Cytochrome ba 3 catalyzes the reductions of oxygen (O 2 ) to water (H 2 O) and of nitric oxide (NO) to nitrous oxide (N 2 O), as well and the oxidation of carbon monoxide (CO) to carbon dioxide (CO 2 ) [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. The photolyzed ba 3 -CO species is an excellent model for time-resolved spectroscopic studies [7,8,9,13,15,18,24].…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome ba 3 catalyzes the reductions of oxygen (O 2 ) to water (H 2 O) and of nitric oxide (NO) to nitrous oxide (N 2 O), as well and the oxidation of carbon monoxide (CO) to carbon dioxide (CO 2 ) [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. The photolyzed ba 3 -CO species is an excellent model for time-resolved spectroscopic studies [7,8,9,13,15,18,24]. In the past, we used time-resolved Raman and step-scan FTIR (TRS 2 -FTIR) spectroscopy to probe the binding of CO to Cu B and the structural changes of the ring-A propionate of heme a 3 and D372 [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] In addition to pH detection, the researches of protonated and deprotonated processes give a chance to view the structure-property relationship for functional dyes deeply. [6,7] Hydrogen bond plays an important role not only in the life process [8][9][10] but also in the construction of molecular systems. [11][12][13] Studies have shown that the formation of hydrogen bonds can inhibit the rotation between molecules, which can effectively immobilize the molecular structure, [14] and not only have an impact on the material melting point, boiling point, solubility, viscosity and other properties, [15] but also contribute to the nonradiative energy transitions of the excited state molecules, thus increasing the radiation transition.…”
Section: Introductionmentioning
confidence: 99%